THE ROLE OF TEACHERS IN CULTIVATING COURTESY AND POLITENESS CHARACTER AMONG FIFTH-GRADE STUDENTS AT MI ROUDLOTUL MUBTADIIN KEDIRI - Rofi'i, Fathur; Khotib, Moh; Pahlawati, Fatimatuszuro (Program Studi Pendidikan Agama Islam, 2025)
In the Islamic perspective, character is synonymous with morals, and morals are synonymous with personality. Character formation is influenced by three environmental aspects. The shift in the culture of politeness has spread to all sectors, even schools in various locations. For example, schools no longer incorporate Javanese cultural values. Some simply convey material without attempting to translate these cultural values, which have become beliefs, into everyday practice. This is also true for fifth-grade students at Roudlotul Mubtadiin, Mojo, Kediri. Therefore, special attention and concrete efforts are needed from the educational environment. This research uses qualitative methods, focusing on an in-depth description of a phenomenon. Researchers understand a phenomenon from the perspective of the research subjects. Data obtained in the form of words, including interviews, observations, and documents, are then analyzed in depth. This study concluded that Akidah Akhlak Learning has a central role in shaping and developing the personality of students in MI Roudlotul Mubtadiin Grade V. This success depends on the synergy between teaching methods that are in accordance with the principles of the Prophet Muhammad SAW, directed learning objectives, teacher role models, and support from the school and family environment. The role of Akidah Akhlak teachers in installing the character values of politeness includes the dimensions of role models, education, training, direction, and evaluation that are carried out continuously and consistently.